Combined In-Fermenter Extraction and Cross-Flow Microfiltration for Improved Inclusion Body Processing - Chew, Tin Lee; Morreale, Giacomo; Middelberg, Anton P. J. (Wiley-Blackwell, 2004)
In this study we demonstrate a new in-fermenter chemical extraction procedure that degrades the cell wall of Escherichia coli and releases inclusion bodies (IBs) into the fermentation medium. We then prove that cross-flow microfiltration can be used to remove 91% of soluble contaminants from the released IBs. The extraction protocol, based on a combination of Triton X-100, EDTA, and intracellular T7 lysozyme, effectively released most of the intracellular soluble content without solubilising the IBs. Cross-flow microfiltration using a 0.2 m ceramic membrane successfully recovered the granulocyte macrophage-colony stimulating factor (GM-CSF) IBs with removal of 91% of the soluble contaminants and virtually no loss of IBs to the permeate. The filtration efficiency, in terms of both flux and transmission, was significantly enhanced by in-fermenter BenzonaseÂ® digestion of nucleic acids following chemical extraction. Both the extraction and filtration methods exerted their efficacy directly on a crude fermentation broth, eliminating the need for cell recovery and resuspension in buffer. The processes demonstrated here can all be performed using just a fermenter and a single cross-flow filtration unit, demonstrating a high level of process intensification. Furthermore, there is considerable scope to also use the microfiltration system to subsequently solubilise the IBs, to separate the denatured protein from cell debris, and to refold the protein using diafiltration. In this way refolded protein can potentially be obtained, in a relatively pure state, using only two unit operations.